Стрес та філософія життя Ганса Сельє (до 100-річчя з дня народження) - Радченко, О.М. (Медична гідрологія та реабілітація, 2006)
Развивая теоретические взгляды К. Бернара и У. Кеннона, Ганс Хьюго Бруно Селье (1907-1982) создал теорию стресса, которая надолго опередила развитие научной мысли того времени. Г.Селье рассмотрел с позиций теории стресса организацию жизни отдельного человека и общества в целом, сформулировал кодекс поведения для достижения счастья, цель жизни и пути ее достижения. Hans Hugo Bruno Selye (1907-1982) continued theoretical ideas of C.Bernard and W.Cannon and created the famous stress theory, which was much ahead of that time science. H. Selye considerate a life organization of a separate person and complete society from the position of his stress theory. He also formulated some behavior rules for reaching the individual happiness. H.Selye stated the main aims of life and proposed ways of their achievement.